Photobleached Oxidative Degradation of Melanins: Chemical Characterization of Melanins Present in Alpaca Fiber. (4th September 2021) - Wakamatsu, Kazumasa; Munyard, Kylie; Oddie, Carolyn; Ito, Shosuke
Abstract: In order to characterize the phenotype and to examine the effects of sun exposure on the color and structure of eumelanin (EM) and pheomelanin (PM) in alpaca fibers, we applied Soluene‐350 solubilization, alkaline hydrogen peroxide oxidation (AHPO) and hydroiodic acid (HI) hydrolysis to the base and tip fibers of 20 true‐black (TB) and 20 warm‐black (WB) alpacas. We analyzed absorbances at 500 nm (A500) and 650 nm (A650), Free and Total pyrrole‐2, 3, 5‐tricarboxylic acid (PTCA), 2, 3, 4, 5‐tetracarboxylic acid (PTeCA) as degradative products from EM, and 4‐amino‐3‐hydroxyphenylalanine (4‐AHP), 3‐amino‐4‐hydroxyphenylalanine (3‐AHP) and thiazole‐2, 4, 5‐tricarboxylic acid (TTCA) as degradative products from PM. We found that the ratio of PTeCA/Total PTCA increased significantly from the base to the tip in both colors of alpaca fibers, while the ratios of A650/A500 and 4‐AHP/3‐AHP decreased significantly. These results show that structures made of both EM and PM in alpaca fibers are modified significantly by sun exposure inducing color change. This study indicates that the ratios of A650/A500, PTeCA/Total PTCA and 4‐AHP/3‐AHP are highly sensitive markers of color change and photodegradation of EM and PM, respectively. Abstract : In order to characterize the phenotype and to examine the effects of sun exposure on the color and structure of eumelanin (EM) and pheomelanin (PM) in alpaca fibers, we applied the chemical analyses to the base and tip fibers of true‐black (TB) and warm‐black (WB) alpacas. The analyses of degradative products showed that structures made of EM and PM from the base to the tip in both colors of alpaca fibers are modified significantly by sun exposure inducing color change.